Development of Ground Organic Monolith Particles as Packing Material in High Performance Liquid Chromatography. (7th January 2020) - Kim, Yune Sung; Kim, Jeong Soo; Sun, Genlin; Cheong, Won Jo
Abstract : Organic monolith particles and their chromatography performance.